Ginger Pye - Estes, Eleanor (San Diego Harcourt, 2000)
The disappearance of a new puppy named ginger and the appearance of a mysterious man in a mustard yellow hat bring excitement into the lives of the pye children
American Corner
Winner Of The John Newbery Medal Book
11
Keywords: English Fiction; English Stories